Sustaining civil society : economic change, democracy, and the social construction of citizenship in Latin America - Oxhorn, Philip (Pennsylvania State University Press, 2011)
"Devoting particular emphasis to Bolivia, Chile, and Mexico, proposes a theory of civil society to explain the economic and political challenges for continuing democratization in Latin America"--Provided by publisher